The Effect of Different Starter Cultures of Lactobacillus paracasei M104 and Pediococcus pentosaceus M103 on the Physicochemical and Microbial Qualities of Fermented Goat Milk - Widodo Widodo; Aryo Pujo Sakti; Ari Surya Sukarno; Endang Wahyuni; Nurliyani Nurliyani (Faculty of Animal Science Universitas Brawijaya, 2019)
The utilization of starter cultures is vital for dairy fermentation industries. Lactobacillus paracasei M104 and Pediococcus pentosaceus M103 have been isolated from goat milk and were demonstrated to acidify goat milk during fermentation. This study was conducted to compare the physicochemical and microbial qualities of goat milk fermented using these starter cultures either as a single starter or combined in goat milk. The treatments were L. paracasei M104 (Lp) and P. pentosaceus M103 (Pp) as single starter culture fermentation and combined (Lp/Pp) fermentation at a ratio of 1:1 at 6% inoculation (v/v). For control treatment, goat milk was fermented using yogurt starter, i.e., a combination culture of Streptococcus thermophilus and L. bulgaricus (St/Lb) at a ratio of 1:1 at 6% (v/v). The fermentation was performed by incubating the inoculated goat milk at 37°C for 18 h. The pH and degree of acidity were measured every 2 h during the fermentation process, whereas the physicochemical (pH, degree of acidity, lactose, protein, and viscosity) and microbial (total lactic acid bacteria/LAB) qualities were measured after the fermentation process. Data analysis revealed that the different starter cultures had no significant effect (P > 0.05) on the pH and degree of acidity, lactose and protein content, viscosity, and total LAB content. The goat milk fermented in this study had an average pH of 4.41 ± 0.11 and a degree of acidity of 1.26 ± 0.05%, a lactose content of 5.47± 0.80%, a protein content of 6.69± 1.52%, a viscosity of 1217 ± 395 cP, and a total LAB content of 9.57 ± 1.49 log CFU/mL. In conclusion, goat milk fermented using both single and combined starter cultures of L. paracasei M104 and P. pentosaceus M103 exhibited similar physicochemical and microbial qualities and required longer fermentation time compared with the control.